Comparison of torsional amplitudes between emmetropes and myopes using after-image slides - Antony Arokiadass Baskaran; Tanuja Britto; Sundaresan Rajkumar; Philip A Thomas; C A Nelson Jesudasan (Indian Journal of Ophthalmology, 2019)
Purpose: To describe the influence of corrected refractive error on measured torsional fusional amplitudes (TA) by comparing the TA between emmetropes and spectacle corrected myopes, using the after-image slides of the synoptophore, as targets. Methods: Fifty emmetropes (Group I) and 50 myopes (Group II) with best-corrected acuity of 6/6 in each eye were included in the study. Near point of convergence (NPC), near point of accommodation (NPA), and horizontal fusional amplitudes (HFA) were assessed in all the subjects. After-image slides, both horizontally aligned, were used as targets (without the bright flashes). One of the slides was rotated inwards, till cyclo-diplopia was reported by the subject; the procedure was repeated with the slide rotated outwards. The sum of the two readings was taken as TA. NPC, NPA, HFA, and TA were analyzed. Results: There was no significant difference in the NPC, NPA, and HFA between the two groups. The emmetropic subjects had significantly better torsional amplitude (8.4 ± 1.4 degrees) compared to myopes (7.7 ± 1.5 degrees, P = 0.03). We postulate that this difference may be due to perceived image minification, which brings the edges of retinal image of the targets closer to the fovea, thus rendering the myopes lesser tolerant to cyclodiplopia than emmetropes. Conclusion: Refractive error, corrected with spectacles, influences the measured TA. Myopic subjects have lesser torsional fusional amplitude than emmetropes.